PENGARUH PENDIDIKAN AKIDAH AKHLAK BERBASIS KETELADANAN, PEMBIASAAN, DAN PENGAWASAN TERHADAP PEMBENTUKAN KARAKTER ISLAMI PESERTA DIDIK - Zaitun Abidin (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2026)
This study aimed to analyze the effects of role modeling, habituation, and supervision in moral education on the development of students’ Islamic character at MTs Al-Kifayah. This study employed a quantitative approach using a qualitative design. The population consisted of all 82 students at MTs Al-Kifayah. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis involved descriptive statistics, simple linear regression, and multiple linear regression. The findings indicated that role modeling had a positive and significant effect on students’ Islamic character, contributing 34.3% to its variance. Habituation also had a positive and significant effect, contributing 41.2%, making it the most dominant factor. Supervision had a positive and significant effect, contributing 35.8%. Simultaneously, role modeling, habituation, and supervision significantly influenced students’ Islamic character, with a coefficient of determination of 65.0%. These findings demonstrate that Islamic character development is more effective when moral education is implemented integratively through exemplary behavior, habituation of positive conduct, and continuous supervision. Accordingly, this study proposes the Modeled–Habituated–Supervised (MHS) framework as an integrative approach to strengthening students’ Islamic character.